Across the Sahara Tracks, Trade and Cross-Cultural Exchange in Libya - Braun, Klaus; Passon, Jacqueline; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This open access book provides a multi-perspective approach to the caravan trade in the Sahara during the 19th century. Based on travelogues from European travelers, recently found Arab sources, historical maps and results from several expeditions, the book gives an overview of the historical periods of the caravan trade as well as detailed information about the infrastructure which was necessary to establish those trade networks. Included are a variety of unique historical and recent maps as well as remote sensing images of the important trade routes and the corresponding historic oases. To give a deeper understanding of how those trading networks work, aspects such as culturally influenced concepts of spatial orientation are discussed. The book aims to be a useful reference for the caravan trade in the Sahara, that can be recommended both to students and to specialists and researchers in the field of Geography, History and African Studies.
Foreword by Prof. Dr. Mohammend Jerary -- Introduction -- Across the vast land -- A journey through time -- Traders, Nomads and Slaves -- Navigating and mapping the "white spot" -- On major trans-Saharan trails -- Places of Trade, Communication and Religion - Important Oases -- Bibliography.
Keywords: Africa -- Economic conditions; Human geography; Africa, North -- History; Geographic information systems; Ethnology -- Africa; Culture; African Economics; Human Geography; History of North Africa; Geographical Information System; African Culture